Karakteristik Risiko Kesehatan Non-Karsinogenik Akibat Pajanan PM2,5 di Tempat-Tempat Umum Kota Jakarta - Pangestika, Rismawati; Wilti, Ikhwan Ridha (Jurnal Kesehatan Lingkungan Indonesia, 2021)
Latar belakang: Jakarta merupakan salah satu kota metropolitan yang mengalami penurunan kualitas udara. Salah satu komponen udara yang berbahaya bagi kesehatan adalah Particulat Matter 2,5 (PM2,5). Berdasarkan data Air Quality Index pada Oktober 2019, kualitas udara Jakarta setara dengan konsentrasi PM2,5 sebesar 87,9 µg/m3 yang melebihi ambang batas yaitu 65 µg/m3. Tujuan penelitian ini adalah untuk menganalisis risiko non-karsinogenik akibat paparan PM2,5 di sekitar tempat-tempat umum kota Jakarta.Metode: Penelitian ini berupa penelitian deskriptif menggunakan studi Analisis Risiko Kesehatan Lingkungan (ARKL) untuk mengetahui tingkat risiko atau Risk Quotient (RQ) pajanan PM2,5 pada radius 0-20 meter setiap lokasi. Jika nilai RQ>1 maka dikategorikan tidak aman, sedangkan nilai RQ≤1 dikategorikan aman.Hasil: Konsentrasi PM2,5 di semua lokasi secara rata-rata masih di bawah baku mutu. Tingkat risiko pajanan PM2,5 berdasarkan perhitungan asupan atau intakedibandingkan dengan hasil analisis dosis-respon rata-rata dikategorikan aman terutama di masjid dan taman kota. Sedangkan di lokasi lainnya memiliki tingkat risiko pajanan yang dikategorikan tidak aman pada radius 10 meter dari pintu masuk stasiun, titik awal di pintu masuk terminal, dan radius 10 meter dari pintu gerbang sekolah yang memiliki nilai RQ>1 tertinggi.Simpulan: Beberapa tempat umum masih memiliki risiko tidak aman akibat pajanan PM2,5 terhadap gangguan kesehatan, sehingga strategi pengelolaan diperlukan untuk menurunkan risiko gangguan kesehatan pada masyarakat dan peningkatan kualitas udara. ABSTRACTTitle: Health Risks Assessmet for Non-Carcinogenic PM2,5 Exposure in Public Places in JakartaBackground: Jakarta is a metropolitan city that has experienced a decline in air quality. One component of air that is harmful is Particulat Matter 2,5 (PM2,5). Based on Air Quality Index data in October 2019, Jakarta's air quality is equivalent to a PM2,5 oncentration of 87,9 μg/m3 which exceeds the threshold of 65 μg / m3. The purpose of this study is to analyze the non-carcinogenic risk due to PM2,5 exposure around public places in the city of Jakarta.Method: This research is a descriptive study using the Environmental Health Risk Analysis (EHRA) study method to determine the level of risk or Risk Quotient (RQ) of PM2.5 exposure at 0-20 meters in each location.. If the value of RQ> 1 is categorized as unsafe, while the value of RQ≤1 is categorized as safe.Result: PM2.5 concentrations in all locations were on average still below the quality standard. The level of risk of PM2.5 exposure based on the calculation of intake or intake compared with the results of the average dose-response analysis is considered safe in mosques and park. Meanwhile, other locations have an exposure risk level that is categorized as unsafe at a radius of 10 meters from the station entrance, the starting point at the terminal entrance, and a radius of 10 meters from the school gate that has the highest RQ>1.Conclusion: Some public places still have an insecure risk due to PM2.5 exposure to health problems, so management strategies are needed to reduce the risk of health problems in the community and increasing air quality. ABSTRACTTitle: Health Risks Assessmet for Non-Carcinogenic PM2,5 Exposure in Public Places in JakartaBackground:Jakarta is a metropolitan city that has experienced a decline in air quality. One component of air that is harmful is Particulat Matter 2,5 (PM2,5). Based on Air Quality Index data in October 2019, Jakarta's air quality is equivalent to aPM2,5 oncentration of 87,9 μg/m3 which exceeds the threshold of 65 μg / m3. The purpose of this study is to analyze the non-carcinogenic risk due to PM2,5 exposure around public places in the city of Jakarta.Method: This research is a descriptive study using the Environmental Health Risk Analysis (EHRA) study method to determine the level of risk or Risk Quotient (RQ) of PM2.5 exposure at 0-20 meters in each location.. If the value of RQ> 1 is categorized as unsafe, while the value of RQ≤1 is categorized as safe.Result:PM2.5 concentrations in all locations were on average still below the quality standard. The level of risk of PM2.5 exposure based on the calculation of intake or intake compared with the results of the average dose-response analysis is considered safe in mosques and park. Meanwhile, other locations have an exposure risk level that is categorized as unsafe at a radius of 10 meters from the station entrance, the starting point at the terminal entrance, and a radius of 10 meters from the school gate that has the highest RQ>1.Conclusion:Some public places still have an insecure risk due to PM2.5 exposure to health problems, so management strategies are needed to reduce the risk of health problems in the community and increasing air quality.